Improving Students Reading Skill by Using Scanning Technique - Efarni; Syahriani, Ririn; Aradhanawaty, Syenja (Mataoleo: Journal of English Education and Linguistics, 2025)
This research was conducted to find out whether the use of scanning technique can improve students' reading skills at SMPN 14 Kendari or not. The research question is "whether the scanning can improve students' reading skills at SMPN 14 Kendari. This study used a quantitative method of pre-experimental design, namely one group pre-test-post-test. The populations of this research were 194 students. Samples were taken using purposive sampling consisting of 30 students. The research instrument was a reading test consisting of 9 multiple choice items. The data collected by giving an initial test to see the students' initial reading ability, the treatment was carried out for four meetings, and the final test was conducted to determine students' reading ability. The results showed that in the pre-test and post-test the significant value of the students was 0.000 which is smaller than alpha (0.05) and the significant level of the line df = 29. In addition, the effect size of the use of scanning techniques is 0.83 and categorized as high level. It can be concluded that H0 was rejected and H1 was accepted. Thus, there was a positive increase in the use of scanning technique in improving students' reading skills.